Pyloric Caeca Number as a Growth-Associated Trait Provides a New Strategy for Selective Breeding in Mandarin Fish (Siniperca chuatsi) - Jingyun Feng; Lijuan Cai; Zhi Zhu; Yixi Tao; Gang Xu; Yang Xue; Xuliang Zhai; Huiqing Mei; Xiaomin Miao; Hao Xu; Yun Li (Fishes, 2025)
Mandarin fish (Siniperca chuatsi) is a commercially important species in China. The number of pyloric caeca, essential for digestion and nutrient absorption, varies considerably (198–386) among individuals, but its relation to growth remains unclear. In this study, 300 samples from the first filial generation (F1) of farmed wild stocks were reared for 56 days and grouped based on pyloric caeca number. Fish with more pyloric caeca (≥289) exhibited significantly higher weight gain rates (WGRs), specific growth rates (SGRs), and digestive enzyme activities compared to those with fewer caeca (≤229). The final body weight (FBW) and the WGR showed moderately positive correlations with caeca number. These results showed that pyloric caeca number may be a valuable trait for selective breeding. To explore its genetic basis, a genome-wide association study (GWAS) identified over 1.4 million SNPs across 24 chromosomes. Twelve SNPs were potentially associated with pyloric caeca number, and we successfully identified one SNP that could effectively distinguish groups with the extreme number of pyloric caeca. Candidate genes near significant loci were enriched in pathways related to cell proliferation, differentiation, and metabolic regulation. These findings suggest a potential association between pyloric caeca number and growth, providing a possible reference for future molecular breeding in mandarin fish.